Finance capitalism and Germany's rise to industrial power - Fohlin, Caroline, 1966- (Studies in macroeconomic history., 2007)
This book uses theoretically-motivated econometric analysis to understand the structure, performance, and influence of universal banks and securities markets on industrial firms during industrialization. The findings show that securities markets can thrive within a civil-law, universal-bank system and suggest that financial system complexity can favor rapid industrial expansion.